2015
DOI: 10.1016/j.jallcom.2015.08.246
|View full text |Cite
|
Sign up to set email alerts
|

Understanding oxygen adsorption on 9.375 at. % Ga-stabilized δ-Pu (111) surface: A DFT study

Abstract: Plutonium (Pu) metal reacts rapidly in the presence of oxygen (O), resulting in an oxide layer that will eventually have an olive green rust appearance over time. Recent experimental work suggested that the incorporation of gallium (Ga) as an alloying impurity to stabilize the highly symmetric high temperature δ-phase lattice may also provide resistance against corrosion/oxidation of plutonium. In this paper, we model a 9.375 at. % Ga stabilized δ-Pu (111) surface and investigated adsorption of atomic O using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Extended X-ray fine structure studies have shown the formation of Ga oxide structures within the Pu oxide, leading to possible disruption of the PuO 2 structure . Recent density functional theory (DFT) studies indicate that Ga will slow down the adsorption of oxygen (O) on Pu–Ga alloy surfaces, leading to possible changes in oxide formation kinetics. , Other recent experimental studies exploring the growth of the native oxide on δ-Pu metal have shown formation of an amorphous oxide structure . What effects impurities might have in the observed amorphous growth remain undetermined.…”
Section: Introductionmentioning
confidence: 99%
“…Extended X-ray fine structure studies have shown the formation of Ga oxide structures within the Pu oxide, leading to possible disruption of the PuO 2 structure . Recent density functional theory (DFT) studies indicate that Ga will slow down the adsorption of oxygen (O) on Pu–Ga alloy surfaces, leading to possible changes in oxide formation kinetics. , Other recent experimental studies exploring the growth of the native oxide on δ-Pu metal have shown formation of an amorphous oxide structure . What effects impurities might have in the observed amorphous growth remain undetermined.…”
Section: Introductionmentioning
confidence: 99%
“…The WIEN2k parameters are kept consistent with previous adsorption studies on a pure δ-Pu and δ-Pu–Ga surface. ,, The WIEN2k parameters are muffin tin radii (RMT) of 1.127, 1.032, and 0.318 Å for Pu, Ga, and H, respectively, and a plane-wave kinetic energy cutoff of K max 2 = 212 eV for the expansion of the wave function within the interstitial region. Because of previous theoretical studies ,, and a k-point convergence test on the surface, a k-point mesh of 2 × 4 × 1 and a temperature broadening parameter of k B T = 0.068 eV are chosen. The convergence criteria for the total energy and charge are 1.36 × 10 –4 eV and 1 × 10 –3 e – , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…% Ga). The stability of these surfaces is discussed in refs and and concludes that increasing Ga content in the surface increases surface stability of δ-Pu.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations